COMPLICATIONS OF THYROIDECTOMY FOR BENIGN DISEASE - Qureshi, Zaheeruddin; Qureshi, Imran; Ahmed, Rashid; Ali, Mumtaz; Iqbal, Tariq (Journal of Ayub Medical College Abbottabad, 2001)
Background: Goitre is a common ailment seen in mountainous regions, like the periphery of Abbottabad. Thyroidectomies are very common in our center. Methods: This study was done to find out the complication rate of thyroidectomies. Results: 189 cases were operated in Ayub Hospital Complex, Abbottabad during July 96 and Dec. 99. All patients were with benign disease and any case found to have malignancy were excluded from the study. The overall complication rate for all the categories was 15%. In total 5 patients died within one month of surgery.